Internet de servi?os - Vaz, Agostinho Manuel (2011)
This work studies the main features of Internet services architectures. It also studies some approaches already proposed for this paradigm of Internet of the Future. The dynamic and flexible construction of applications, from the autonomous combination of different distributed services is one of the objectives of the Internet Services. Thus, a Conceptual Services Internet Architecture is proposed that allows the services to discover each other, establish contracts and self-organize in a distributed and transparent way.